Experiment study on the performance of the solid desiccant energy recovery system - Wathan, Hpu Pwint (2015)
The demand for air-conditioning became widely dispersed all over the world due to the extreme change in climatic conditions, which causes energy consumption in high quaintly. In order to provide best indoor air quality, energy efficiency of the HVAC system, and the minimum energy consumption, renewable energy system is installed along with HVAC system. Desiccant coated heat recovery wheel has the ability to enhance the dehumidification performance of HVAC systems, which will lead to the improvement in the quality of the indoor air. Meanwhile, the energy recovery wheel can reduce the overall energy consumption. In this final year project, an experimental performance study has been done on the solid desiccant wheel. The operation principles and the energy recovery process of the desiccant wheel has been researched and the operating performance of the desiccant wheel exchanging heat and moisture between supply and exhaust air streams and the effects of the various parameters on the performance of the recovery system have been observed. The performance of the NI LabVIEW software has been verified by comparing the results obtained by the software. Using the LabVIEW software, the performance of the rotary dehumidifier is studied by examining the moisture removed by process area in the desiccant wheel. The effect of the air velocity of the fans on the desiccant wheel has also been studied.